2004
DOI: 10.1677/erc.0.0110295
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in human insulinoma tissue: genes involved in the insulin secretion pathway and cloning of novel full-length cDNAs.

Abstract: Insulinoma is a clinically common cause of organic hypoglycemia. The prominent characteristic of insulinoma is endogenous hyperinsulinism. Until now, the molecular biology of human insulinoma has been little understood. In this study, gene expression profiling of human insulinoma was established by expressed sequence tag (EST) sequencing and cDNA array. A total of 2063 clones were obtained, of these, 1589 clones were derived from EST sequencing, 975 clones were derived from cDNA array and 501 clones were share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
(30 reference statements)
2
22
0
2
Order By: Relevance
“…In previous studies of our group, cDNA libraries of human hypothalamus, pituitary, adrenal and insulinoma tissues were established and several novel full-length cDNAs cloned [25,26]. A novel full-length cDNA cloned from human hypothalamus tissue was selected for further study and found to be related with glucose metabolism (X. Wang and R. Hu, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of our group, cDNA libraries of human hypothalamus, pituitary, adrenal and insulinoma tissues were established and several novel full-length cDNAs cloned [25,26]. A novel full-length cDNA cloned from human hypothalamus tissue was selected for further study and found to be related with glucose metabolism (X. Wang and R. Hu, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Several novel genes were cloned from the cDNA library, and their nucleic acid and amino acid sequences were submitted into GenBank (Wang et al 2004). Among the novel genes, INM02 was selected for extensive study.…”
Section: Discussionmentioning
confidence: 99%
“…Another large-scale effort, termed Secreted Protein Discovery Initiative, utilized multiple gene-identification strategies and identified more than 1000 novel secreted and transmembrane proteins (Clark et al 2003). In previous studies of our group, cDNA libraries of human hypothalamus, pituitary, adrenal, and insulinoma tissues were established and several novel full-length cDNAs were cloned (Hu et al 2000, Wang et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Além da sua participação em diversas doenças neurodegenerativas e inflamatórias, as isoformas da proteína 14-3-3 já foram relacionadas com tumorigênese tanto como possíveis supressores de tumor quanto como oncogenes, tendo sido associadas ainda, com a baixa sobrevivência de pacientes com câncer (Toyo-Oka; Shionoya et al, 2003;Wilker e Yaffe, 2004;Porter;Khuri et al, 2006;Kilani;Maksymowych et al, 2007). Em particular a 14-3-3ζ está superexpressa em inúmeras linhagens celulares de câncer de pulmão e em tecidos de pacientes com câncer de pulmão (Qi;Liu et al, 2005;Fan;Zhao et al, 2008;Zang;Li et al, 2010), além de ter sido relacionada com sua resistência à anoikis, uma forma de morte celular programada que é induzida por células dependentes de ancoragem separando-se da matriz extracelular circundante, e promovendo, consequentemente, um crescimento livre de ancoragem Zhao et al, 2008). Intrigantemente, como já foi descrito pelo nosso grupo, a linhagem celular APM é capaz de formar esferóides e proliferar em condição independente de ancoragem ).…”
Section: Discussionunclassified
“…Estes resultados foram obtidos não somente in vitro, mas o grupo também mostrou que a administração oral de aspirina foi capaz de diminuir os níveis plasmáticos de dermcidin e restaurar os níveis de insulina. Intrigantemente, esta proteína nunca havia sido descrita em insulinomas, estando de acordo com o fato muito bem caracterizado da liberação excessiva e/ou descontrolada de insulina por células de insulinoma e nesidioblastoses (Kaczirek;Soleiman et al, 2003;Xu et al, 2004). Também de acordo com este fato, a linhagem APM não apresenta secreção de insulina induzida por glicose, como nosso grupo mostrou previamente , o que pode ser, ao menos em parte, devido aos níveis aumentados de dermcidin nestas células.…”
Section: Discussionunclassified